2000
DOI: 10.1128/aac.44.5.1291-1295.2000
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Assessment of Cefprozil against Streptococcus pneumoniae : Implications for Breakpoint Determinations

Abstract: Cefprozil, an oral semisynthetic cephalosporin, is commonly utilized in the treatment of respiratory-tract infections in children. While this agent has provided acceptable clinical success over a number of years, this study was undertaken to better define its pharmacodynamic profile against Streptococcus pneumoniae. Nineteen clinical isolates of S. pneumoniae were utilized in the neutropenic murine thigh infection model. To simulate the pharmacokinetic profile of cefprozil in children, the renal function of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Numerous studies have demonstrated that this index value is independent of the dosing interval, animal species, site of infection, or the cephalosporin used as long as free drug levels are considered (1,2,5,11,17,18). In these studies as well, the %TϾMIC associated with efficacy was similar in the thigh and lung infection models.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Numerous studies have demonstrated that this index value is independent of the dosing interval, animal species, site of infection, or the cephalosporin used as long as free drug levels are considered (1,2,5,11,17,18). In these studies as well, the %TϾMIC associated with efficacy was similar in the thigh and lung infection models.…”
Section: Discussionsupporting
confidence: 51%
“…A variety of in vitro and in vivo studies have demonstrated that the killing activity of beta-lactam antibiotics is not enhanced by exposure to drug concentrations far exceeding the MIC (1,4,11,13,14,17,18). Furthermore, PAE studies have demonstrated minimal persistent effects with drugs from the beta-lactam class with most bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in Fig. 1, differences in the growth control are inherent in in vivo studies, due to natural variations between isolates, and similar growth differences have been published previously (11). Results obtained through analyses of these current gatifloxacin data reveal that all the pharmacodynamic parameters were correlated; however, the AUC/MIC ratio was the best predictor of success for both outcome parameters studied.…”
Section: Discussionmentioning
confidence: 71%
“…Also, the size of rabbit used (4.75¡0.5 kg) permitted the use of equipment, instruments and techniques intended for clinical paediatric practice, and the rabbits tolerated the daily BAL and blood sampling well. In contrast to previous reports [27,28], the present study used immunocompetent animals, which made pneumonia development more natural. The strain of S. pneumoniae used in the present study was a clinical isolate with a common serotype, and inoculated rabbits were observed over a comparatively long period of time (up to 96 h after inoculation).…”
Section: Discussionmentioning
confidence: 77%